(untitled) (Revista de Biología Marina y Oceanografía, 2023)
The fish community inhabiting mesophotic coral ecosystems (MCE) at Corales de Profundidad National Natural Park (CPNNP), Colombian Caribbean Sea was described. Most of the species (89%) are common in shallow reef environments of an adjacent Marine Protected Area. Halichoeres maculipinna, Prognathodes aculeatus, Serranus luciopercanus and Lactophrys trigonus were recorded for the first time at CPNNP. The healthy and highly resilient characteristics of MCE is confirmed with the taxonomic composition of the found fishes. The information presented in this study provides data and techniques that help to complement the baseline of fish’s assemblages associated with mesophotic coral ecosystems in the Colombian Caribbean Sea.